2016
DOI: 10.2298/fil1606601h
|View full text |Cite
|
Sign up to set email alerts
|

The existence of solution for a k-dimensional system of fractional differential inclusions with anti-periodic boundary value conditions

Abstract: We investigate the existence of solutions for a k-dimensional systems of fractional differential inclusions with anti-periodic boundary conditions. We provide two results via different conditions for obtaining solutions of the k-dimensional inclusion problem. We provide some examples to illustrate our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…, n), k : J × R → R, and μ, η : C(J, R) → R satisfy certain conditions. It is clear that equation 5is a special case of inclusion (1), where K(t, x(t)) = {k(t, x(t))}. With argument similar to the proof of Theorem 11, and applying Theorem 8, we can prove the following theorem.…”
Section: Theorem 11mentioning
confidence: 89%
See 1 more Smart Citation
“…, n), k : J × R → R, and μ, η : C(J, R) → R satisfy certain conditions. It is clear that equation 5is a special case of inclusion (1), where K(t, x(t)) = {k(t, x(t))}. With argument similar to the proof of Theorem 11, and applying Theorem 8, we can prove the following theorem.…”
Section: Theorem 11mentioning
confidence: 89%
“…During the last decade, the subject of fractional differential equations and inclusions has been developed intensively (for example, see [1][2][3][4][5][6][7][8] and the references therein). An excellent account on the study of fractional differential equations can be found in [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The main reasons for using a fractional-order system (FDE) is related to systems with memory, history, or nonlocal effects which exist in many biological systems that show the realistic biphasic decline behavior of infection or diseases but at a slower rate. It has been studied by many researchers that fractional extensions of mathematical models of integer order represent the natural fact in a very systematic way such as in the approach of Etemad et al [13][14][15], Hedayati et al [13,[16][17][18][19], Baleanu et al [11,18,20,21], and Mahdy et al [22,23]. In recent years, many papers have been published on the subject of Caputo-Fabrizio fractional derivative (see, for example, [24][25][26][27][28][29][30]).…”
Section: Introductionmentioning
confidence: 99%
“…(see [1][2][3][4][5][6][7][8][9][10][11]). Many researchers helped in developments on the existence and uniqueness results of fractional differential equations [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Stability is a notion in physics, and most phenomena include the concept.…”
Section: Introductionmentioning
confidence: 99%